Description of Silvinichthys pedernalensis n. sp. (Teleostei, Siluriformes) from the Andean Cordillera of southern South America - Fernández, L.; Sanabria, E. A.; Quiroga, L. B. (Animal Biodiversity and Conservation, 2017)
Silvinichthys pedernalensis, a new species, is described from an Andean stream in Provincia San Juan, Argentina, based on its coloration pattern, and its meristic, morphometric and osteological characters. S. pedernalensis differs markedly from all other known members of the genus Silvinichthys as a result of the combination of the absence of pelvic girdle and fin, the wide supraorbital bone, the number of interopercle odontodes 14–18, the number of opercular odontodes 6–8, the branched pectoral–fin rays 7, the dorsal–fin rays 11, the number of dorsal pterygiophore 7, the branchiostegal rays 6, the dorsal procurrent caudal–fin rays 14 and ventral 15, the ribs 16, the vertebrae 39, the dark marmorated pigmentation on the body and head, the head depth 9.9–12.2% SL, the interorbital wide 28.3–36.1% HL, the nasal barbel length 27.3–39.0% SL, the maxillary barbel length 39.5–61.7% SL, the submaxillary barbel length 24.7–41.9% SL, the snout length 40.6–44.4% HL, the body depth 10.1–12.6% SL, the anal base fin 10.2–11.7% SL, and the caudal peduncle length 19.3–21.5% SL.